An empirical study on the effects of an enterprise fan page. Issue 3 (3rd July 2018) - Shang, Shari S.C.; Hsu, Wei-Yen; Tseng, Hsiao-Ting; Jiang, Jen Jen; Chiang, Chieh-Jen
ABSTRACT: Most major enterprises have invested in social networking to provide services, promote products, or communicate with customers. However, to date, no clear understanding on the effects of social networks on business performance has emerged. This study examines the relationship between the capability of the enterprise to manage social networks and the resultant benefits of their investing in the social network. A fan page on Facebook is the selected target of study. By analyzing the effort required to manage a fan page, we measured the fan-page managing capability by its number of fans. Then, we proposed six hypotheses for empirical examination of the causal relationship between enterprises' social network managing capability and business benefits. The study applied two-stage data collection and testing. The first stage is to build a general understanding of the relationship between the number of fans and business revenue. Based on findings of the first stage, the study tested the hypotheses on selected global firms and sought patterns of benefits generated from the fan page. This study builds deep understanding from various aspects about fan-page effects on enterprises, and proposes that firms that provide products and services with characteristics of low-product price, short-product durability, and low-customer involvement are empirically influenced by the management of their fan pages.